(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper delves into the realm of sustainable interventions designed to enhance the development and well-being of adolescents and youth. The transitional period from childhood to adulthood is marked by significant physical, cognitive, emotional, and social changes. As this phase carries both opportunities and challenges, implementing interventions that cater to the unique needs of adolescents and youth is crucial. This paper explores a variety of sustainable interventions, considering their effectiveness, ethical considerations, and long-term impacts on individuals and society. The paper also examines the role of technology, community involvement, and education in supporting the successful implementation of these interventions. By shedding light on evidence-based practices, this research contributes to the broader discourse on fostering positive youth development and creating a sustainable future.